Palatability and Stability Studies to Optimize a Carvedilol Oral Liquid Formulation for Pediatric Use - Blanca Chiclana-Rodríguez; Encarnacion Garcia-Montoya; Miquel Romero-Obon; Khadija Rouaz-; Anna Nardi-Ricart; Marc Suñé-Pou; Josep M. Suñé-Negre; Pilar Pérez-Lozano (MDPI AG, 2023)
Carvedilol (CARV) is a blocker of α- and β- adrenergic receptors, used as an "off-label" treatment for cardiovascular diseases in pediatrics. Currently, there is no marketed pediatric-appropriate CARV liquid formulation, so its development is necessary. Palatability (appreciation of smell, taste, and aftertaste) is a key aspect to be considered during the development of pediatric formulations since only formulations with good palatability also have adequate acceptability in this population. Consequently, the aim of this research was to assess the palatability and acceptability of different CARV formulations using an in vivo taste assessment (ID Number PR103/22) in order to select the highest palatability-rated CARV formulation. The preparation of CARV formulations was based on a reference 1 mg/mL CARV solution, which contains malic acid as a solubilizing agent. Subsequently, sucralose and flavoring agents were added and mixed until complete dissolution to the corresponding formulations. Adult volunteers participated in this study and evaluated the taste and odor of various CARV formulations through a questionnaire and a sensory test. The mean palatability score, measured on a 10-point scale, increased from 1.60 for the unflavored control to 7.65 for the highest-rated flavored formulation. Moreover, the bitterness of the optimized CARV formulation was reduced from 66.67% to 17.86%, and the taste pleasantness was increased from 25/100 to 73/100. This optimized CARV formulation contains a sweetening agent, sucralose, in addition to two flavoring agents at appropriate concentrations for pediatrics. Furthermore, the physicochemical and microbiological stability of the optimized CARV formulation were evaluated for 6 months at 25, 30, and 40 °C, in addition to in-use stability for 15 days at 25 °C, whose results were confirmed. Thus, we successfully developed a palatable CARV liquid solution that contains excipients appropriate for pediatrics and is stable under the studied conditions.